SELF-ASSESSMENT OF THE IMPORTANCE AND ATTAINABILITY OF SUPERVISORS’ ETHICAL COMPETENCE IN LATVIA - Angena, Anna; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Code of Ethics of Supervisors’ in Latvia is currently being developed and it is important to understand how Supervisors themselves evaluate professional ethical competence. The aim of this study is to find out what is the Self-Assessment of the Importance and Attainability of Supervisors’ Ethical Competence in Latvia. The research questions were the following: 1) What is the self-assessment of the importance and attainability of Supervisors’ ethical competence in Latvia? 3) Are there differences in the self-assessment of the importance and attainability of Supervisors’ ethical competence in Latvia and if so, what they are? 3) Are there differences in the self-assessment of the importance and attainability of Supervisors’ ethical competence in Latvia between supervisors with different work experience and if so, what they are? The participants of this study were 48 supervisors with practice experience in different professional fields. Two forms were filled out online: 1) demographical data form; 2) self-assessment of the importance and attainability form. Self-assessment forms were evaluated on a 5-pont Likert scale. For data analysis the descriptive statistical methods, Kolmogorov-Smirnov test and Wilcoxon signed-rank test were used. The results showed that the supervisors’ ethical competence is evaluated as very and quite important and fully and mostly attainable. The results indicated statistically significant differences in 13 out of 16 supervisors’ ethical competence that was evaluated higher in importance than attainability.